Inflationsberechnung: Zinspolitik der EZB wird als Inflationstreiber statistisch nicht erfasst - Johannes Schwanitz (Wirtschaftsdienst, 2024)
– After ten consecutive increases in the prime rate by the European Central Bank's (ECB), the question arises: What significance do these measures have, both indirectly for the interest rates increased at all value-added levels on the corporate side, and for households? While the prices for rents, being the largest component, are factored into inflation calculations, the dramatically increased interest rates for real estate loans - specifically for owner-occupied housing - are not considered at all. In this article, an extension of the calculation scheme is demonstrated to make transparent the direct effect of the prime rate increase on real estate owners' expenses.
Keywords: E31; E43; E47; 330; Zinspolitik; Inflationsrate; Zinspolitik; Inflationsrate